Atlas of fluorencein angiography - Alex E Jalkh (W. B. Saunders, 1992)
Fluorescein angiography is a technique widely used to study the chorioretinal circulation and the pathology affecting the retina and choroid. The book is intended to familiarize the ophthalmologist and retina specialist-in-training in the practical aspects of fluorescein angiography and in the basics of interpretation of fluorescein angiograms. It includes common disorders of the retina, retinal pigment epithelium,a nd choroid. It offers information and guidelines that are helpful in differentiating fluorescein angiography findings characteristic of specific disease processes